Ovid's lovers : desire, difference and the poetic imagination - Rimell, Victoria; Ovidius Naso, P. (Cambridge : Cambridge University Press, 2006)
Central to Ovid's elegiac texts and his Metamorphoses is his preoccupation with how desiring subjects interact and seduce each other. This major study, which shifts the focus in Ovidian criticism from intertextuality to intersubjectivity, explores the relationship between self and other, and in particular that between male and female worlds, which is at the heart of Ovid's vision of poetry and the imagination. A series of close readings, focusing on both the more celebrated and less studied parts of the corpus, moves beyond the more often-asked questions of Ovid, such as whether he is 'for' or 'against' women, in order to explore how gendered subjects converse, compete and co-create. It illustrates how the tale of Medusa, alongside that of Narcissus, reverberates throughout Ovid's oeuvre, becoming a fundamental myth for his poetics. This book offers a compelling, often troubling portrait of Ovid that will appeal to classicists and all those interested in gender and difference.
Introduction: Narcissus and Medusa: desiring subjects and the dialectics of Ovidian erotics -- Specular logicis: Medicamina -- Double vision: Ars Amatoria I, II, and III -- Seeing seers: Metamorphoses 10-11.84 -- Co-creators: Heroides 15 -- What goes around: Heroides 16-21 -- Space between: Heroides 18-19 -- Conclusion.
Julkaistu myös verkkoaineistona.
Keywords: Ovidius Naso, P; antiikki; kirjallisuudentutkimus; latinankielinen kirjallisuus; antiken; litteraturvetenskap; litteratur på latin